A Phase 2 Study of Pimodivir (JNJ-63623872) in Combination With Oseltamivir in Elderly and Nonelderly Adults Hospitalized With Influenza A Infection: OPAL Study . (1st July 2020) - O'Neil, Brian; Ison, Michael G; Hallouin-Bernard, Marie Charlotte; Nilsson, Anna C; Torres, Antoni; Wilburn, John M; van Duijnhoven, Wilbert; Van Dromme, Ilse; Anderson, David; Deleu, Sofie; Kosoglou, Teddy; Vingerhoets, Johan; et al.
Abstract: Background: Both the elderly and individuals with comorbidities are at increased risk of developing influenza-related complications. Novel influenza antivirals are required, given limitations of current drugs (eg, resistance emergence and poor efficacy). Pimodivir is a first-in-class antiviral for influenza A under development for these patients. Methods: Hospitalized patients with influenza A infection were randomized 2:1 to receive pimodivir 600 mg plus oseltamivir 75 mg or placebo plus oseltamivir 75 mg twice daily for 7 days in this phase 2b study. The primary objective was to compare pimodivir pharmacokinetics in elderly (aged 65–85 years) versus nonelderly adults (aged 18–64 years). Secondary end points included time to patient-reported symptom resolution. Results: Pimodivir pharmacokinetic parameters in nonelderly and elderly patients were similar. Time to influenza symptom resolution was numerically shorter with pimodivir (72.45 hours) than placebo (94.15 hours). There was a lower incidence of influenza-related complications in the pimodivir group (7.9%) versus placebo group (15.6%). Treatment was generally well tolerated. Conclusions: No apparent relationship was observed between pimodivir pharmacokinetics and age. Our data demonstrate the need for a larger study of pimodivir in addition to oseltamivir to test whether it results in a clinically significant decrease in time-to-influenza-symptom alleviation and/or the frequency of influenza complications. Clinical trials registration: NCT02532283 . Abstract : Pharmacokinetic parameters of pimodivir are similar between nonelderly adult and elderly patients with influenza A infection.